Clinical Characteristics and Endoscopic Management of Duodenal Lipomas: 10-Year Experience from a Tertiary Center in China - Xiang, Jingyuan; Chai, Ningli; Li, Longsong; Xu, Ning; Wang, Pengju; Cheng, Yaxuan; Linghu, Enqiang (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Duodenal lipomas are rarely found in the gastrointestinal tract. Most published literature referring to the tumors is limited to case series. There remained issues about the understanding and management of duodenal lipomas to be clarified. We aimed to investigate the clinical and endoscopic features of duodenal lipomas. Additionally, outcomes of endoscopic resection for duodenal lipomas were evaluated. Materials and Methods: A total of 29 duodenal lipomas resected endoscopically from December 2011 to October 2021 were included. Clinical characteristics, endoscopic features, and endoscopic ultrasound findings were analyzed retrospectively. The endoscopic resection was performed in 3 ways: hot snare polypectomy, endoscopic mucosa resection, and endoscopic submucosal dissection. Results: Of the 29 duodenal lipomas, 21 were located at the second portion with a mean size of 25.8 mm (range, 7-60 mm). Yamada type IV was the most common macroscopic type in 14 lesions, exhibiting a tendency of forming large peduncles. Seven patients had digestive symptoms. The occurrence of symptoms is associated with the tumor size. Endoscopic ultrasound was performed on 23 duodenal lipomas, of which 20 demonstrated homogenous echogenicity and 3 presented heterogeneous with tubular anechoic region. The endoscopic resection operation was successfully conducted on 29 patients without severe adverse events. The rate of en bloc and endoscopic complete resection was 93.1% and 86.2%, respectively. Recurrence was noted in 1 patient. Conclusion: Clinical characteristics with typical endoscopic ultrasound features are helpful in duodenal lipomas diagnosis. The endoscopic resection is a safe and effective treatment for duodenal lipomas with considerable long-term outcomes. Cite this article as: Xiang J, Chai N, Li L, et al. Clinical characteristics and endoscopic management of duodenal lipomas: 10-year experience from a tertiary center in China. Turk J Gastroenterol. 2023;34(7):720-727.